Development of nap neurophysiology: preliminary insights into sleep regulation in early childhood. (2nd June 2016) - Kurth, Salome; Lassonde, Jonathan M.; Pierpoint, Lauren A.; Rusterholz, Thomas; Jenni, Oskar G.; McClain, Ian J.; Achermann, Peter; LeBourgeois, Monique K.
Summary: Although all young children nap, the neurophysiological features and associated developmental trajectories of daytime sleep remain largely unknown. Longitudinal studies of napping physiology are fundamental to understanding sleep regulation during early childhood, a sensitive period in brain and behaviour development and a time when children transition from a biphasic to a monophasic sleep–wakefulness pattern. We investigated daytime sleep in eight healthy children with sleep electroencephalography (EEG) assessments at three longitudinal points: 2 years (2.5–3.0 years), 3 years (3.5–4.0 years) and 5 years (5.5–6.0 years). At each age, we measured nap EEG during three randomized conditions: after 4 h (morning nap), 7 h (afternoon nap) and 10 h (evening nap) duration of prior wakefulness. Developmental changes in sleep were most prevalent in the afternoon nap (e.g. decrease in sleep duration by 30 min from 2 to 3 years and by 20 min from 3 to 5 years). In contrast, nap sleep architecture (% of sleep stages) remained unchanged across age. Maturational changes in non‐rapid eye movement sleep EEG power were pronounced in the slow wave activity (SWA, 0.75–4.5 Hz), theta (4.75–7.75 Hz) and sigma (10–15 Hz) frequency ranges. These findings indicate that the primary marker of sleep depth, SWA, is less apparent in daytime naps as children mature. Moreover, our fundamental data provide insight into associations between sleep regulation and functional modifications in the central nervous system during early childhood.